Brief Report: A Counselling-Friendly Alternative to the DSM-5? A Review of The Power Threat Meaning Framework - Strong, Tom (Canadian Journal of Counselling and Psychotherapy, 2019)
The British Psychological Society’s Clinical Division (2018) recently published The Power Threat Meaning Framework, an evidence-supported discussion document to promote consideration of alternatives to functional psychiatric diagnosis. I summarize the general content and approach of the framework as a meaning-focused alternative to the psychiatric classification system, the Diagnostic and Statistical Manual of Mental Disorders – Fifth Edition (American Psychiatric Association, 2013). I comment on the utility of the Power Threat Meaning Framework for the conversational practice of a nonmedicalized approach to counselling.